Transcriptomic and proteomic insights into feather keratin degradation by Fervidobacterium - Javier-López, Rubén; Kielbasa, Mélodie; Armengaud, Jean; Birkeland, Nils-Kåre (Frontiers in Microbiology, 2025)
Keratin, one of the most recalcitrant and abundant proteins on Earth, constitutes a challenging and underutilized material for the poultry industry. Although it resists degradation by most commonly available enzymes, natural breakdown occurs through the action of certain fungi and bacteria. This process remains poorly understood, and only a few thermophilic and anaerobic bacteria are known to effectively degrade keratin. Some members of the genus Fervidobacterium have been demonstrated to be effective at degrading feather keratin under high temperatures and anoxic conditions. However, a comprehensive evaluation of their keratinolytic capabilities remains lacking, leaving their potential largely underexplored. In this study, we assessed the keratinolytic activity of all available Fervidobacterium strains. Six strains were active against this recalcitrant substrate, namely Fervidobacterium changbaicum CBS-1T, Fervidobacterium islandicum H-21T, Fervidobacterium pennivorans T, Fervidobacterium pennivorans DSM9078T, Fervidobacterium sp. GSH, and Fervidobacterium sp. 21710. These bacteria were used in a comparative proteomics analysis, grown with either glucose or chicken feathers as the sole carbon source. Similarly, the three most efficient strains, Fervidobacterium pennivorans T, Fervidobacterium sp. GSH, and Fervidobacterium islandicum H-21T underwent an in-depth comparative transcriptomics analysis. Among the numerous upregulated proteins and overexpressed genes identified when comparing feather-grown to glucose–grown cells, oxidoreductases and peptidases are key enzymes in the degradation process, suggesting their potential application in enzymatic keratinolytic cocktails for degrading feather keratin.